Risk Factors of Anthrax Transmission in Pacitan Regency - Yudied Agung Mirasa; Eko Winarti; Adelita Setiawan; Olievia Rachma Akhsani (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: Anthrax was a zoonotic disease caused by the bacterium Bacillus anthracis in several regions of Indonesia. Transmission of anthrax in animals and humans occurred by direct contact with anthrax spores present in meat, soil, or plants. This study aimed to analyse the risk factors and recommend preventive action for anthrax transmission. Methods: This research used a descriptiveanalytic study to describing cases based on the case definition, primary data, and secondary data. The primary data were collected from the field observations and interviews with farmers and people in the community. The secondary data were obtained from the Pacitan District Health Office and Surabaya Technical Centre for Environmental Health and Disease Control. Data analysis of this study applied content analysis techniques that describe the actual situation of the community. Results and Discussion: Risk factors for anthrax transmission in Pacitan Regency included livestock traffic from endemic anthrax areas and lacked public knowledge about anthrax disease, rainfall, and topography. Conclusion: Anthrax disease control measurements include surveillance and investigation periodically, treatment of the suspected livestock, vaccination, disinfection, and socialisation. The government needs to control livestock traffic by providing proper regulation. Also, the public might improve knowledge and awareness with their livestock